Pengaruh Disiplin Kerja, Kesehatan dan Keselamatan Kerja (K3), dan Kompensasi Terhadap Kinerja Pegawai Perspektif Ekonomi Islam (Studi Pada Pegawai Main Office PT Kanindo Makmur Jaya) - Yuda, Alif Putra; Suharnomo, Suharnomo (ITB AAS INDONESIA Surakarta, 2024)
The aim of this research is to examine the influence of work discipline, occupational health and safety (K3), and compensation on the performance of PT Head Office employees. Kanindo Makmur Jaya, sampling from the population was determined using non-probability sampling and the sample size was 96 respondents. The method used to analyze the data is multiple linear regression analysis. The results obtained show that work discipline, occupational health and safety (K3), and compensation influence employee performance.